English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please give me the answer and the steps to find the answer (srry i'm giving this question im just bored)

2006-11-18 06:49:45 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

Since we're given y = x+8, let's solve the first equation for x by plugging in y.

3x*3y=y*x^2+96 <==> 3x*3(x+8)=(x+8)*x^2+96
Move everything to one side and expand.
(x+8)*x^2+96-3x*3(x+8) = 0
x^3+8x^2 -9x^2 -24x + 96 = 0
x^3 - x^2 -24x + 96 = 0

This is easiest solved by plugging in to the solver of a graphic calculator. Once you get values for x, plug in to y = x + 8 and you have values for y.

2006-11-18 06:50:43 · answer #1 · answered by Anonymous · 0 0

3x*3y=y*x^2+96
y=x+8 substitute

3x*3(x+8)=(x+8)x^2+96 distribute where necessary
9x^2+72x=x^3+8x^2+96 subtract LHS from both sides
0=x^3-x^2-72x+96 there is at leasr 1 real root. 1 will be somewhere between 1 & 2. around 1.35
y will be x+8= around 9.35

2006-11-18 14:57:11 · answer #2 · answered by yupchagee 7 · 0 0

3x*3y = y*x^2 +96
y=x+8
x = y - 8
9y(y - 8) = y(y - 8)^2 + 96
9y^2 - 72y = y(y^2 - 16y + 64) + 96
9y^2 - 72y = y^3 - 16y^2 + 64y + 96
y^3 - 25y^2 + 136y + 96 = 0
y ≈ -0.630873981

2006-11-18 15:51:44 · answer #3 · answered by Helmut 7 · 0 0

3x*3(x+8)=(x+8)*x^2+96
9x^2+72x=x^3+8x^2+96
x^3-x^2-72x+96=0
solve to get x and substitute in y=x+8 to get y
the values of x are -8.63 or 8.29
so y will be -0.63 or +16.29

2006-11-18 15:01:06 · answer #4 · answered by raj 7 · 0 0

fedest.com, questions and answers